Management of Travel Booking in the Light of Destination Marketing: Evidence from an Alpine Indian State - Sikkim - Batabyal, Debasish; Das, Dillip Kumar (Indian Journal of Marketing, 2013)
India has many idyllic Himalayan hill stations. The formulation of appropriate development and marketing strategy for all those destinations is the need of the hour. Sikkim is a small hilly state with immense potentiality. It is bounded by vast stretches of Tibetan plateau in the North, the Chumbi Valley and the kingdom Bhutan in the East, the kingdom of Nepal in the west, and Darjeeling (West Bengal) in the South. The study has touched upon a number of theoretical and empirical issues relating to the formulation of travel booking and thereby contributing to the destination marketing strategies for the appropriate development of tourism in Sikkim in the backdrop of the present market conditions in India and abroad.